ANOTHER VIEW ON HIV/AIDS TESTING AT THE WORKPLACE PFG Building Glass (Pty) Ltd v Chemical Engineering Pulp Paper Wood & Allied Workers Union (2003) 24 ILJ 974 (LC) - Tamara Cohen (Obiter, 2022)
In the third of a trilogy of cases (the first two being Joy Mining Machinery (A division of Harnischfeger (SA) (Pty) (Ltd) v NUMSA (2002) 23 ILJ 391 (LC) and Irvin and Johnson Ltd v Trawler and Line Fishing Union (2003) 24 ILJ 565 (LC)) interpreting the boundaries of section 7(2) of the Employment Equity Act 55 of 1998 (hereinafter referred to as “EEA”), the Labour Court in PFG Building Glass (Pty) Ltd v Chemical Engineering Pulp Paper Wood & Allied Workers Union ((2003) 24 ILJ 974 (LC)) (hereinafter referred to as “PFG Building Glass (Pty) Ltd v CEPPWAWU) has yet again approached the issue of HIV/Aids testing at the workplace from a different perspective. In this case the applicant sought a declarator pronouncing that authorisation for the anonymous and voluntary testing of employees for HIV/Aids at the workplace was unnecessary, as such testing does not fall within the scope of section 7(2) of the EEA. Section 7(2) of the EEA expressly prohibits the testing of an employee to establish HIV/Aids status, unless such testing is “determined to be justifiable by the labour court …” A similar order was sought and granted in the earlier decision of Rogers AJ in Irvin and Johnson Ltd v Trawler and Line Fishing Union (supra) on different grounds. Unlike Rogers AJ in Irvin and Johnson Ltd v Trawler and Line Fishing Union (supra), Pillay J in PFG Building Glass (Pty) Ltd v CEPPWAWU (supra) chose to interpret this provision on the grounds identified by section 3 of the EEA, being “compliance with the Constitution, so as to give effect to its purpose, taking into account any relevant code of good practice … and compliance with international law obligations …”